A case study of transdisciplinarity and biomimicry: The restoration of water systems using eco-machines within the informal Berg River community - Wolfaardt, Gabriel (Stellenbosch : Stellenbosch University, 2017)
Thesis (MPhil)--Stellenbosch University, 2017.